Wybrane instrumenty polityki handlowej samorządu miasta Leszna - Chudak, Mariusz (Chosen Tools of Trade Policy on the Example of the City of Leszno, 2007)
The aim of this paper is an attempt of the general presentation and assessment of main assumptions of the trade policy of Leszno on the basis of documents ratified by the Parish Council. The author also presents own proposal of an expertise taking into account social, economic, and spatial problems that are characteristic for this form of the economic activity. The paper presents a detailed analysis of the strategy of the development of Leszno of the year 1997, the study of conditionings and directions for the spatial development of the city (2000) and local spatial planning for the period 1995-2005.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1161, s. 318-327